2012
DOI: 10.1158/1078-0432.ccr-11-2683
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MEK and PI3K/mTOR Suppresses Tumor Growth but Does Not Cause Tumor Regression in Patient-Derived Xenografts of RAS-Mutant Colorectal Carcinomas

Abstract: Purpose: Gene mutations along the Ras pathway (KRAS, NRAS, BRAF, PIK3CA) occur in approximately 50% of colorectal cancers (CRC) and correlate with poor response to anti–EGF receptor (EGFR) therapies. We assessed the effects of mitogen-activated protein (MAP)/extracellular signal-regulated kinase (ERK) kinase (MEK) and phosphoinositide 3-kinase (PI3K)/mTOR inhibitors, which neutralize the major Ras effectors, in patient-derived xenografts from RAS/RAF/PIK3CA-mutant metastatic CRCs (mCRC). Experim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
121
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(135 citation statements)
references
References 29 publications
(39 reference statements)
12
121
0
Order By: Relevance
“…It was recently demonstrated that mTOR inhibitors have anti-tumor effects (Bijnsdorp et al, 2011;Finn., 2012;Migliardi et al, 2012). However, our study failed to determine the relationship between the expression of P-S6 (S235/236), DEPTOR and overall survival in CRC.…”
Section: Discussionmentioning
confidence: 80%
“…It was recently demonstrated that mTOR inhibitors have anti-tumor effects (Bijnsdorp et al, 2011;Finn., 2012;Migliardi et al, 2012). However, our study failed to determine the relationship between the expression of P-S6 (S235/236), DEPTOR and overall survival in CRC.…”
Section: Discussionmentioning
confidence: 80%
“…In preclinical models, inhibiting the PI3K pathway showed synergy with cytotoxic agents, enhancing its efficacy by potentiating apoptosis (41). In addition, dual inhibition of the RAF/MEK and PI3K/AKT/mTOR pathways seems to be required for complete abrogation of downstream effectors in RASmutant tumors (19)(20)(21). PIK3CA and PTEN mutations strongly reduce the sensitivity of RAS-mutant cells to MEK inhibitors (42).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to highlight the fact that the use of full doses of both targeted agents was rarely achieved because of overlapping toxicities. Interestingly, in patient-derived metastatic colorectal cancer xenografts exhibiting KRAS and BRAF mutations, concomitant inhibition of PI3K/ mTOR and MEK pathway activity proved to be more effective than single pathway inhibition, although the best response was limited to tumor growth arrest rather than overt tumor regression (21). This observation is potentially important for further drug development in RAS/RAFmutant colorectal cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, KRAS mutations are frequent in human cancer and are generally considered to be "actionable," as the oncogene addiction model predicts that treatment of such patients with a MEK inhibitor (a kinase downstream of KRAS) would deliver clinical benefit. However, in both preclinical models of KRAS-mutant cancers and in early clinical studies, responses of KRAS-mutant tumors to MEK inhibitors have proven to be modest (14)(15)(16). It will therefore be important to define more unambiguously what the term "actionable" means.…”
mentioning
confidence: 99%